PENGEMBANGAN PARIWISATA HALAL DI JALUR LINTAS SELATAN TULUNGAGUNG - Masruroh, Siti (Program Studi Ekonomi Syariah, 2025)
This research analyze potential of sustainable tourism development and religious moderation as a strategy to create halal tourism. In this study, halal tourism focuses not only on providing services that comply with sharia principles, but also on strengthening interfaith harmony that can support the sustainability of the tourism industry. This research highlights the importance of a moderate understanding of religious teachings that can encourage harmonious social interactions so as to create an environment conducive to the development of halal tourism destinations. By utilising local potential and involving the community in the management of tourism resources, it is expected to improve the economic welfare of the community while maintaining spiritual and cultural values. This research also explores the challenges faced in the implementation of halal tourism, such as the lack of facilities that support the needs of Muslim tourists. Thus, the development of halal tourism in the Tulungagung Southern Crossing is expected to be a model for other regions in combining economic sustainability with religious values, thus creating a tourist destination that is not only naturally attractive but also socially and spiritually meaningful